Blastic plasmacytoid dendritic cell neoplasia (BPDC) in elderly patients: results of a treatment algorithm employing allogeneic stem cell transplantation with moderately reduced conditioning intensity - Dietrich, Sascha; Andrulis, Mindaugas; Hegenbart, Ute; Schmitt, Thomas; Bellos, Frauke; Martens, Uwe M.; Meißner, Julia; Krämer, Alwin; Ho, Anthony Dick; Dreger, Peter (Biology of blood and marrow transplantation, 2011)
Blastic plasmacytoid dendritic cell neoplasm (BPDC), formerly known as blastic NK cell lymphoma, is a rare hematopoietic malignancy preferentially involving skin, bone marrow, and lymph nodes. The overall prognosis of BPDC is dismal, with a median overall survival (OS) of only 12 to 14 months despite aggressive chemotherapy. Anecdotal reports suggest that younger patients might benefit from myeloablative therapy with autologous or allogeneic stem cell transplantation (alloSCT). However, with a median age at diagnosis beyond 60 years, BPDC primarily affects elderly patients. Here, we present for the first time evidence that also in elderly patients, alloSCT for BPDC is feasible and may result in sustained remission if conditioning with moderately reduced intensity is used. Between 2006 and 2009, 6 patients were treated at our institution who fulfilled the diagnostic criteria for BPDC. Median age was 67 (range: 55-80) years. All responded to acute leukemia-type induction therapy. Whereas 2 patients who were ineligible for alloSCT rapidly died of disease recurrence, 4 patients underwent alloSCT from unrelated donors as part of first-line (n = 1) or salvage treatment (n = 3). Two patients allografted in remission live disease free 57 and 16 months post-alloSCT, whereas 2 patients transplanted with active disease achieved complete remission but relapsed 6 and 18 months after transplantation, respectively. In conclusion, reduced-intensity conditioning (RIC) alloSCT from unrelated donors is feasible and seems to be effective in elderly patients with BPDC, suggesting that alloSCT should be pursued aggressively in patients with this otherwise fatal disease up to 70 years of age.
Gesehen am 10.06.2022